FACTORS AFFECTING STUDENTS’ SPEAKING ANXIETY: A MIXED METHOD STUDY OF THE THIRD-YEAR STUDENT OF ENGLISH DEPARTMENT AT UNIVERSITY RIAU - Sinaga, Fitta Verolina; Daud, Afrianto; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research analyses about the factors contributing to speakinganxiety among third-year students in the English Department at University Riau. It also explores strategies that can help reduce this anxiety and enhance students’ ability to communicate effectively in English. Speaking anxiety is a common challenge faced by learners of English as a foreign language, often stemming from fear of judgment, lack of confidence, and inadequate preparation. These factors not only hinder students’ participation in class but also impede their overall language acquisition process. Employing a mixed-method approach, the study collected data from 115 participants using the Foreign Language Speaking Anxiety Scale (FLSA) questionnaire and semi- structured interviews. The findings revealed that over half of the participants (53.33%) reported experiencing “very anxious” levels of speaking anxiety, indicating the prevalence and severity of the issue. Students identified specific causes of their anxiety, including fear of making mistakes, being evaluated negatively by peers and instructors, and feelings of linguistic inadequacy. To address these challenges, the study identified several strategies that students found effective. Among these were thorough preparation before speaking tasks, consistent practice to build familiarity and fluency, and adopting a positive mindset to reduce fear and build self-assurance. These strategies were found to significantly alleviate anxiety and enable students to approach speaking activities with greater confidence and ease.Keywords: Speaking anxiety, English proficiency, mixed-method, students' confidence